2019
DOI: 10.1111/jvh.13086
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of hepatitis D virus genotype‐1 in Europe allows classification into subtypes

Abstract: Summary Hepatitis delta virus (HDV) is an RNA virus which leads to both acute and chronic forms of hepatitis. At present, HDV isolates have been classified into eight major genotypes distributed over different geographical regions. Recent increase in HDV sequences in Europe and worldwide has enabled us to revisit the taxonomic classification of HDV. A total of 116 large hepatitis delta antigen (L‐HDAg) nucleotide sequences and 13 full‐length HDV genome sequences belonging to genotype‐1 from our European cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…These two recent studies are important since they reported the introduction of new viral strains to Europe by immigration as previously discussed (88,89). In the Middle East, mainly HDV I was isolated from patients with HDV infection (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)78). Studies from Turkey (34)(35)(36)(37)(38)(39) and Israel (78) exclusively detected HDV I.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…These two recent studies are important since they reported the introduction of new viral strains to Europe by immigration as previously discussed (88,89). In the Middle East, mainly HDV I was isolated from patients with HDV infection (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)78). Studies from Turkey (34)(35)(36)(37)(38)(39) and Israel (78) exclusively detected HDV I.…”
Section: Discussionmentioning
confidence: 80%
“…In European countries, HDV I, II, and African genotypes were detected in patients with HDV infection (11, 33, 45-47, 66, 69-71, 77, 82). In detail, in Albania (71), Germany (33,66), Greece (71), Italy (33,(45)(46)(47), Romania (47,69), and Spain (33,70), only HDV I was isolated. In the study by Ivaniushina et al (82) in Russia, in addition to HDV I, HDV II was observed, which is justified with the fact that the study was conducted in Yakutia located in the east of Russia, a region near the Chinese borders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneity and viral evolution HDV shows great genetic variance, a broad range of viral quasispecies exist within the same infected individual 5 . The intragenotypic genetic variability of HDV genotype 1 is estimated at 11.3-14.3% 36 , and recently, a subclassification of genotypes has been proposed 37 .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“… 5 The intragenotypic genetic variability of HDV genotype 1 is estimated to be 11.3–14.3% 36 and, recently, a subclassification of genotypes was proposed. 37 …”
Section: Heterogeneity and Viral Evolutionmentioning
confidence: 99%